Challenges in Translating German Comics Nerd Girl Into Indonesian - Shivana, Eqtsani Alfatkhus; Agustina, Widya; Usman, Rizman (Nexus Publishing NXP, 2025)
Nerd Girl is a German comic by Sarah Burrini. This study examines the challenges that arise in translating the German comic Nerd Girl into Indonesian. Comics as visual literary works require translators to maintain a balance between linguistic, cultural, and visual aspects. The main objective of this study is to identify forms of incompatibility between the source text (SL) and target text (TL), and to describe the translation strategies used. This study uses a qualitative approach with case study methods and content analysis, where data are obtained from the original comic text and the translation results carried out by the researcher herself. The results of the study show that the main challenges include translating idioms, figurative language, slang, cultural references, wordplay, and character speech styles. The translation strategies used include cultural adaptation, the use of functional equivalents, and a contextual approach based on visuals and narrative logic. In conclusion, the success of comic translation depends not only on linguistic accuracy, but also on understanding the cultural context and character characterization.